Referendum odwoławcze w gminie – instytucja wyborców czy wybieranych? - Kowalik, Janina (Political Preferences, 2014)
The subject of discussion in this article is the issue of the referendum repealing the executive authorities in the municipality. In recent years the number of referenda repealing mayors and presidents of cities has significantly increased. Nonetheless, the low effectiveness of theses referendums caused by low voter turnout results surprising. It seems as if the repealing referendums turned from the strongest direct democracy institution into a tool that the potential candidates for mayor use for eliminating from the electoral list people that fulfill these functions for many consecutive years. The lack of effectiveness of the repealing referendums seems to attest to the fact that local communities are rarely willing to participate in such activities. This article contains the results of the surveys on public attitudes towards repealing referendums, as well as the measurement of attitudes towards non-participation in the repealing referendum in order to invalidate them.